Influence of Dance Programmes on Gait Parameters and Physical Parameters of the Lower Body in Older People: A Systematic Review - Rodríguez, Bárbara; Paris-Garcia, Federico (International journal of environmental research and public health, 2022)
(1) Background: The regular practice of dancing benefits the physical condition, improving quality of life and minimising the adverse effects of ageing. Therefore, this review aims to evaluate the impact of dance programmes by quantifying different physical parameters of the lower body in older adults. (2) Methods: A systematic qualitative review in the English language (PubMed, Scopus, OvidSP, Cochrane and PEDro database) until mid-2020 considering the PRISMA guidelines and the PEDro quality criteria considering the following parameters of gait: stride length and width, speed. Physical parameters: flexion and dorsiflexion joint, muscle strength and range of motion were carried out. (3) Results: 9 studies with a population of 544 subjects from 5 continents and 6 types of dances were taken into account. The improvement of some parameters over others depended on the type of dance and the movements generated, having moderate positive effects on strength, agility, mobility and balance. (4) Conclusions: there is a general improvement in the functional capacity of the elderly through the practice of ballroom dancing, with specific improvement of each parameter depending on the type of dance.